Electron Impact Excitation Cross Sections of the $1s2s$ $^3S$ Metastable State of Helium (Journal of Atomic and Molecular Sciences, 2012)
The differential and integral cross sections for the excited states $1s2p$ $^3P,$ $1s3s$ $^3S,$ $1s3p$ $^3P$ and $1s3d$ $^3D$ of helium from the metastable state $1s2s$ $^3S$ are calculated using the relativistic distorted wave method. A systematical comparison is made with theavailable experimental and theoretical results. Better agreement is found when the presentresults are compared with previous calculations and experiments for the integral cross sections. For differential cross sections, our results are in general agreement with the experimental data compared with the previous theoretical values.